European journal of government and economics (Europa Grande, 2012)
"The European Journal of Government and Economics (Online ISSN: 2254-7088) is an international academic journal for peer reviewed research on all aspects of government and economics. EJGE is particularly interested in current issues regarding the interrelationship between the fields of government and economics, from the influence of government on the economy (economic policy) to economic explanations of government (public choice). It is also particularly interested in questions directly or indirectly related to Europe."--Journal homepage.
Keywords: Economics : Europe : Periodicals; Economic policy; Economics; Politics and government; Europe : Economic policy : Periodicals; Europe : Politics and government : Periodicals; Europe